2011
DOI: 10.1111/j.1540-8175.2011.01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Left Ventricular Dysfunction in Asymptomatic Chronic Mitral Regurgitation Patients with Normal Ejection Fraction: A Combined Tissue Doppler and Velocity Vector Imaging-Based Study

Abstract: LV long-axis functions are important markers of LV contractility in MR patients. Novel echocardiographic techniques may provide additional data on subclinical changes in the LV and give way to the optimal timing for the surgery in severe MR patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The clinical use of PW TDI for the assessment of LV mechanical function in horses with valvular regurgitation has not been previously described. In humans and For legend, see Table 3. dogs with valvular regurgitation, it has been suggested that TDI might aid in the detection of subclinical LV dysfunction [31][32][33] and the prediction of increased pulmonary capillary wedge pressure 34 and congestive heart failure. [35][36][37][38] Detection of early subclinical LV dysfunction in horses may provide useful additional information, for example, when investigating horses with murmurs detected on prepurchase examinations or during the evaluation of horses with poor performance.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical use of PW TDI for the assessment of LV mechanical function in horses with valvular regurgitation has not been previously described. In humans and For legend, see Table 3. dogs with valvular regurgitation, it has been suggested that TDI might aid in the detection of subclinical LV dysfunction [31][32][33] and the prediction of increased pulmonary capillary wedge pressure 34 and congestive heart failure. [35][36][37][38] Detection of early subclinical LV dysfunction in horses may provide useful additional information, for example, when investigating horses with murmurs detected on prepurchase examinations or during the evaluation of horses with poor performance.…”
Section: Discussionmentioning
confidence: 99%
“…12 A number of studies also suggest that SR imaging may detect subclinical LV dysfunction in a variety of diseases before LV systolic function was established. 13,14 Yurdakul et al 15 demonstrated that S/SR values of MR severity were decreased. Their study population consisted of 54 patients with isolated non-ischemic MR and 30 healthy aged matched subjects were examined (mild MR n=7, moderate n=29 and severe MR n=18).…”
Section: Discussionmentioning
confidence: 99%